Information technology management governance analysis using cobit 5 (Case study at Universitas Dian Nuswantoro-PSDKU Kediri) - Choerul Umam; Wildan Mahmud; Moch. Sjamsul Hidajat; Ichwan Setiarso (LPPMPK- Universitas Muhammadiyah Cileungsi, 2023)
A higher education facility called Universitas Dian Nuswantoro (UDINUS) is situated in Semarang City, Central Java, at Jl. Imam Bonjol Number 207. In order to offer top-notch educational services in the East Java region, UDINUS established a Study Program Outside the Main Campus (PSDKU) in the City of Kediri. Information technology is used by UDINUS to manage the company. beginning with student services, personnel, funding, and educational infrastructure. There isn't currently a system in place to gauge how effectively information technology administration is being used. In this study, a thorough analysis was done to establish how the COBIT 5 framework should be used for IT management. It is anticipated that by carrying out this research, it will be possible to learn more about the state of IT governance at UDINUS, Kediri City Campus, and offer recommendations to leaders for improvement in order to improve management. method for governing information technology at UDINUS's Kediri Campus. Additionally, the goal of this study is to learn more about the maturity level of the IT Governance program presently underway at the UDINUS campus in Kediri City. The approach taken in this study is a Cobit 5 framework analysis with several stages, including: initiate program (movers within the organization), define problems and opportunities (know the position of IT management in the organization), define road map (improvement goals), and plan program (planning to do). UDINUS Kediri has a value of 2.88 at the Established Process level, which can be interpreted as having an IT governance system maturity level with a value of 2.88, according to the study's conclusion, which was drawn from the findings of the analysis of information technology governance systems using COBIT 5. UDINUS PSDKU Kediri has carried out a description of the objectives and structure in accordance with the established standards at the Established Process level